(untitled) (Nepal Journal of Epidemiology, 2020)
Background: Right to health is one among the important components of basic human rights. The Government of India had announced “Ayushman Bharat for a new India-2022”, during 2018-19 parliament budget sessions with two components namely, Health and wellness centers for strengthening primary care and national health protection scheme now known as Pradhan Mantri Jan Arogya Yojana (PMJAY) for enabling access to secondary and tertiary health care by giving health (6). Current study was conducted to assess awareness and readiness of the health care workers in implementation of Pradhan Mantri Jan Arogya Yojana in tertiary care hospital, in Rishikesh. Material and Methods: A hospital based cross sectional study was conducted with estimated sample size calculated of 236, with treating consultants and residents as study participants. Participants filled a self-administered pretested semi structured questionnaire by which their awareness and readiness in implementing PMJAY was assessed. Data was entered and analyzed using EPI Info 7 software. Result: Total number of respondents was 181. Mean awareness score was 4.5±1.96 and mean readiness score was 16±5. Mean awareness and readiness score among medical and surgical branches was not statistically significant. There was significantly high awareness score among faculty compared to senior residents. Relation between awareness and readiness was found to be correlated with Pearson’s correlation of 0.206 and was statistically significant. Linear regression model demonstrated an increase of 0.531 units in readiness for every unit increase in awareness score. Conclusion: Mean awareness score of the doctors was just around half of maximum possible score. Awareness is more among the faculty members than residents. With increase in awareness there is an increase in readiness among the study population. There is a need to organize workshops on PMJAY for stakeholders.